TRANSFORMATION OF MEDIA JOURNALISM DURING COVID 19 IN INDONESIA - Musfialdy, Musfialdy (Indonesian Journal of Economics, Social, and Humanities, 2024)
ABSTRACT During the COVID-19 pandemic, many media outlets have faced disruption. These disruptions are not only related to health but also to public life and the media industry as a whole. During the COVID-19 pandemic, people made the media the main source of information. The purpose of this research is to find out the transformation of media journalism during COVID-19 in Indonesia. This research uses social information processing theory, which describes how a person develops computer-mediated interpersonal and group communication (online) without non-verbal cues, as well as making it easier and more convenient. The research method uses qualitative methodology with a case study approach. In the atmosphere of the COVID-19 pandemic, where people are traumatized by the rapid and ubiquitous transmission of COVID-19 and social restrictions, communication using computers and smartphones mediated online is one of the right solutions. The conclusion of this research is that the production process of television journalism has changed.